Verbal Abuse Among Theology Students: A Biblical Analysis and Pastoral Response Through Faith-and-Character-Based Christian Education - Rosmiaty Loly; Lenggan Pait; Florence Farida (Jurnal Indonesia Sosial Sains, 2026)
Verbal abuse has become an increasingly concerning issue within higher education environments, including theological institutions, where students are expected to develop spiritual maturity, ethical behavior, and Christ-centered character. Destructive forms of communication—such as insults, sarcasm, labeling, humiliation, and verbal intimidation—can negatively impact students’ psychological well-being, academic participation, self-esteem, and spiritual growth. This study aims to analyze the phenomenon of verbal abuse among theology students through biblical, pastoral, and Christian educational perspectives, using Ephesians 4:29 as the primary theological foundation. A qualitative approach was employed, combining library research with theological-pastoral analysis. Relevant literature from biblical theology, pastoral care, Christian education, psychology, and communication studies was systematically reviewed using content analysis. The study also applied the Pastoral Circle framework, which includes seeing reality, socio-theological analysis, faith reflection, and pastoral action. The findings reveal that verbal abuse not only harms students’ emotional and social well-being but also contradicts Christian communication ethics and the principles of grace-centered relationships. The study concludes that integrating biblical teachings, pastoral care, and faith-based character education is essential to fostering constructive communication, promoting emotional healing, supporting spiritual transformation, and cultivating a healthier campus culture among theology students.